2015
DOI: 10.1038/gt.2015.81
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive tracking of gene transcript and neuroprotection after gene therapy

Abstract: Gene therapy holds exceptional potential for translational medicine by improving the products of defective genes in diseases and/or providing necessary biologics from endogenous sources during recovery processes. However, validating methods for the delivery, distribution and expression of the exogenous genes from such therapy can generally not be applicable to monitor effects over the long term because they are invasive. We report here that human granulocyte colony-stimulating factor (hG-CSF) cDNA encoded in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 41 publications
0
21
0
Order By: Relevance
“…After 30 min of ischemia, the aneurysm clips were removed from both CCAs and the incision was sutured closed. Post-surgery analgesics were administered, and animals could wake up within 10 to 20 min after surgery [26]. All mice subjected to BCAO exhibited a significant reduction in regional cerebral blood flow (RCBF) to 51% pre-BCAO values and the RCBF retuned to 91% of the pre-BCAO level at the beginning of reperfusion as monitored with a Laser Doppler Flowmeter (LDF).…”
Section: Bilateral Common Carotid Artery Occlusion (Bcao)mentioning
confidence: 99%
See 1 more Smart Citation
“…After 30 min of ischemia, the aneurysm clips were removed from both CCAs and the incision was sutured closed. Post-surgery analgesics were administered, and animals could wake up within 10 to 20 min after surgery [26]. All mice subjected to BCAO exhibited a significant reduction in regional cerebral blood flow (RCBF) to 51% pre-BCAO values and the RCBF retuned to 91% of the pre-BCAO level at the beginning of reperfusion as monitored with a Laser Doppler Flowmeter (LDF).…”
Section: Bilateral Common Carotid Artery Occlusion (Bcao)mentioning
confidence: 99%
“…Restoration of blood flow (reoxygenation) was also observed directly under the microscope. Sham-operated controls were subjected to the same surgical procedures except that CCAs were not occluded [26]. The body temperature was monitored and maintained at 37°C ± 0.5°C during surgery and during the immediate postoperative period until the animals recovered fully from anesthesia.…”
Section: Bilateral Common Carotid Artery Occlusion (Bcao)mentioning
confidence: 99%
“…Based on subtraction R2* maps that identified regional repair/remodeling [23, 29, 31], we are able to also identify changes in HDAC5 expression in the chronic paradigm. Figure 11a shows R2* elevation in the LS of three consecutive MR sections (a total of 1.5 mm in the dorsal LS); however, we observed several ROIs in the NAc/Striatal (arrows).…”
Section: Resultsmentioning
confidence: 99%
“…Given that the composition of NVU is the same in the CNS and the retina (1) and that our previous studies demonstrated that BCAO compromises the BRB (7), we delivered chimeric anti‐Rho‐SPION‐Ran (a T2 MR‐CA) through an eyedrop solution administered to the left eye (2 μg Fe in 1.5 μl) of C57black6 mice ( n =3) 1 d after BCAO (2). We acquired MR images of the eyes at 6 time points (each mouse received sequential MRI twice, with an interval of 1.5 h awakeness) and analyzed the R2∗ values using the right eye of the same mouse as the negative control.…”
Section: Resultsmentioning
confidence: 99%
“…Throughout the operation we maintained the animals' body temperature at 36 ± 1 °C using a heating blanket, and we monitored temperature with a rectal thermosensor. We used Doppler analysis to assess the blood flow in the middle cerebral artery in mice that underwent surgical procedures, positioning the Doppler probes to the skull during surgery (7). By the third day after BCAO‐60, all of the surviving postischemic mice exhibited spontaneous activity in their home cages, were responsive to handling, and engaged in normal self‐grooming behavior.…”
Section: Methodsmentioning
confidence: 99%